THE STUDENTS’ PREFERENCES OF ONLINE LEARNING DURING COVID-19 PANDEMIC - Andi Rahmi Utami; Muhammad Asfah Rahman; Maemuna Muhayyang (Universitas Negeri Makassar, 2022)
This research aimed to find out the kind of online learning the students prefer and the reasons why the students prefer the online learning in learning English at SMA Negeri 16 Makassar. This research applied mixed methods research design. The data were collected from the questionnaire and interview. The subject of this study was the second-grade social science students. The questionnaire was conducted on 98 students and the interview was conducted on 12 students. The result of this research showed that the mean score of the students' preference in synchronous was (46,17) indicated